Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Petani Padi (Studi Kasus: Kecamatan Godong, Kabupaten Grobogan) - Cendikia Himawan Tri Nugraha; Nugroho Sumarjiyanto Benedictus Maria (Universitas Diponegoro, 2021)
Godong Subdistrict is one of the riceproducing areas in Grobogan Regency, which has the title as a rice barn in Grobogan Regency with a potential crop level. study aims to determine the effect of land area, capital and labour on farmer’s income. The data used are primary data with a sample size of 98.90 rounded off to 100 farmers. This research used quantitative methods with multiple regression analysis methods. The results showed that the capital variable had a positive and insignificant effect on farmers' income in the fields. In contrast, the variables of land area and labour have a positive and significant effect on income in the rice fields in Godong District, Grobogan Regency. The coefficient of determination (R-square) is obtained at 0.288. The coefficient of R-square means that 28.8% of the dependent variable (income) can be explained by the independent variables, namely capital, land area, and labour. While the remaining 71.2% is explained by other variables outside the model used, such as factors of production, selling price, and the amount of production.